2016
DOI: 10.1016/j.vaccine.2016.03.108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of protection induced by a dengue virus serotype 2 envelope domain III protein scaffold/DNA vaccine in non-human primates

Abstract: We describe the preclinical development of a dengue virus vaccine targeting the dengue virus serotype 2 (DENV2) envelope domain III (EDIII). This study provides proof-of-principle that a dengue EDIII protein scaffold/DNA vaccine can protect against dengue challenge. The dengue vaccine (EDIII-E2) is composed of both a protein particle and a DNA expression plasmid delivered simultaneously via intramuscular injection (protein) and gene gun (DNA) into rhesus macaques. The protein component can contain a maximum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 52 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…This vaccine conferred protection to the vaccinated macaques upon challenge with dengue virus 2, whereas the control animals showed viremia. These results concluded that a neutralizing antibody titer (>1: 6000) provided sterilizing protection in immunized macaques ( 75 ).…”
Section: Dna Vaccine Candidates For Dengue Virusmentioning
confidence: 90%
“…This vaccine conferred protection to the vaccinated macaques upon challenge with dengue virus 2, whereas the control animals showed viremia. These results concluded that a neutralizing antibody titer (>1: 6000) provided sterilizing protection in immunized macaques ( 75 ).…”
Section: Dna Vaccine Candidates For Dengue Virusmentioning
confidence: 90%
“…Accumulating studies have proved that EDIII-based vaccine candidates can elicit specific neutralizing antibodies [38][39][40] Choosing only domain III rather than whole envelope protein could reduce the risk of ADE due to the lack of other non-neutralizing or cross-reactive epitopes. Hence, most of recent efforts have focused on utilization of EDIII to produce a subunit dengue vaccine [41][42][43]. We have constructed a tetravalent domain III in tandem using the Gly4SerGly4 linker, and testified its potential utility in the diagnosis of DENV infections with a high degree of sensitivity and specificity [41].…”
Section: Discussionmentioning
confidence: 99%
“…Another physical method developed to deliver plasmids epidermally is the gene gun [95]. A particle-mediated epidermal delivery (PMED) gene gun was used in preclinical trials to deliver a DNA vaccine against the dengue virus in nonhuman primates.…”
Section: Gene Gunmentioning
confidence: 99%